Small-volume in vitro lipid digestion measurements for assessing drug dissolution in lipid-based formulations using SAXS - Nafia F. Khan; Malinda Salim; Syaza Y. Binte Abu Bakar; Kurt Ristroph; Robert K. Prud'homme; Adrian Hawley; Ben J. Boyd; Andrew J. Clulow (Elsevier, 2022)
Lipid-based formulations improve the absorption capacity of poorly-water-soluble drugs and digestion of the formulation is a critical step in that absorption process. A recent approach to understanding the propensity for drug to dissolve in digesting lipid-based formulations couples an in vitro pH-stat lipolysis model to small-angle X-ray scattering (SAXS) by means of a flow-through capillary. However, the conventional pH-stat apparatus used to measure the extent of lipid digestion during such experiments requires digest volumes of 15-30 mL and drug doses of 50-200 mg, which is problematic for scarce compounds and can require excessive amounts of formulation reagents. This manuscript describes an approach to reduce the amount of material required for in vitro lipolysis experiments coupled to SAXS, for use in instances where the amount of drug or formulation medium is limited. Importantly, this was achieved while maintaining the pH stat conditions, which is critical for maintaining biorelevance and driving digestion to completion. The digestibility of infant formula with the poorly-water-soluble drugs halofantrine and clofazimine dispersed into it was measured as an exemplar paediatric-friendly lipid formulation. Halofantrine was incorporated in its powdered free base form and clofazimine was incorporated both as unformulated drug powder and as drug in nanoparticulate form prepared using Flash NanoPrecipitation. The fraction of triglyceride digested was found to be independent of vessel size and the incorporation of drug. The dissolution of the two forms of clofazimine during the digestion of infant formula were then measured using synchrotron SAXS, which revealed complete and partial solubilisation over 30 min of digestion for the powdered drug and nanoparticle formulations, respectively. The main challenge in reducing the volume of the measurements was in ensuring that thorough mixing was occurring in the smaller digestion vessel to provide uniform sampling of the dispersion medium.